2015
DOI: 10.1038/sc.2015.68
|View full text |Cite
|
Sign up to set email alerts
|

Subjective sleep disturbances and quality of life in chronic tetraplegia

Abstract: Study design: This is a cross-sectional survey. Objectives: The objective of this study was to evaluate the subjective sleep disturbances and quality of life in chronic tetraplegia. Setting: This study was conducted in a community sample from Victoria, Australia. Methods: People with tetraplegia were mailed a survey battery including the following: demographic questions; Karolinska Sleepiness Scale (KSS); Basic Nordic Sleepiness Questionnaire; Functional Outcomes of Sleep Questionnaire (FOSQ); Multivariate Apn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
1
20
2
1
Order By: Relevance
“…Similar conclusions have been reported in other studies in which the poor sleep efficiency has been related to sleep apneas and neuromuscular weakness that negatively affects respiratory function [41][42][43]. In any case, people with tetraplegia suffer sleep problems and poor quality of life [44]; moreover, these problems associated to the increased metabolic disorders (as described in the Introduction) place them in an increased risk for suffering stroke or myocardial infarction. Despite that a pilot clinical trial [45], carried out in eight patients with tetraplegia and absence of MT production, in which sleep disorders existed, showed that treating them with 8 mg of the MT agonist Ramelteon did not produce significant effects on the existing sleep problems, we think that the reported multiple beneficial effects of MT, and the absence of any adverse effect that it might produce, make this hormone useful when treating SCI patients.…”
Section: Discussionsupporting
confidence: 85%
“…Similar conclusions have been reported in other studies in which the poor sleep efficiency has been related to sleep apneas and neuromuscular weakness that negatively affects respiratory function [41][42][43]. In any case, people with tetraplegia suffer sleep problems and poor quality of life [44]; moreover, these problems associated to the increased metabolic disorders (as described in the Introduction) place them in an increased risk for suffering stroke or myocardial infarction. Despite that a pilot clinical trial [45], carried out in eight patients with tetraplegia and absence of MT production, in which sleep disorders existed, showed that treating them with 8 mg of the MT agonist Ramelteon did not produce significant effects on the existing sleep problems, we think that the reported multiple beneficial effects of MT, and the absence of any adverse effect that it might produce, make this hormone useful when treating SCI patients.…”
Section: Discussionsupporting
confidence: 85%
“…Sleep is an essential physiological need that has a critical role for general health. Sleep disturbances are more frequently reported among individuals with spinal cord injury (SCI) compared to healthy individuals, and are associated with negative health outcomes, poor quality of life [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…P1’s score may be associated with poor health in the last four weeks, and the WHOQoL scale refers to this period of time. People with chronic tetraplegia experience more subjective sleep problems and worse quality of life than their able-bodied counterparts [ 39 ]. A study involving 270 individuals who sustained SCI found that poorer QoL was associated with secondary impairments (for example, neuropathic pain, urinary tract infection), activity limitations, and participation restrictions, but not with neurological level, completeness of injury, age, or time since injury [ 11 ].…”
Section: Discussionmentioning
confidence: 99%